Minkowski-space correlators in AdS/CFT correspondence: Recipe and applications - Son, D; Starinets, A (2002)
We formulate a prescription for computing Minkowski-space correlators from AdS/CFT correspondence. This prescription is shown to give the correct retarded propagators at zero temperature in four dimensions, as well as at finite temperature in the two-dimensional conformal field theory dual to the BTZ black hole. Using the prescription, we calculate the Chern-Simons diffusion constant of the finite-temperature N = 4 supersymmetric Yang-Mills theory in the strong coupling limit. We explain why the quasi-normal frequencies of the asymptotically AdS background correspond to the poles of the retarded Green's function of the boundary conformal field theory. © SISSA/ISAS 2002.